1985
DOI: 10.1038/313653a0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the calcium regulatory muscle protein troponin-C at 2.8 Å resolution

Abstract: Crystals of turkey skeletal muscle troponin-C reveal a molecule of two domains with an unusual structure. Two Ca2+ ions are bound to the C-terminal domain. The two cation-binding sites of the regulatory (N-terminal) domain are Ca2+ free; this domain adopts a markedly different conformation from the C-terminal domain. The two domains are connected by a long nine-turn alpha-helix; three of these turns are exposed fully to solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
324
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(341 citation statements)
references
References 39 publications
14
324
0
3
Order By: Relevance
“…SANS studies of the ternary cTn further revealed the effect of phosphorylation of the two protein kinase A dependent phosphorylation sites in the cardiac-specific N-terminal extension in cTnI ($ 27-33 residues); this phosphorylation in known to result in a reduction in myofilament Ca 21 sensitivity and an increase in relaxation and cross-bridging cycle kinetics. [25][26][27] All of the high-resolution structures of sTnC and cTnC show the characteristic dumbbell shape with two globular domains separated by an extended, solvent-exposed helix of 7-8 turns [28][29][30][31][32] 41 and Heidorn and Trewhella 42 presented the first SAXS studies of rabbit sTnC that showed that the two globular domains of sTnC are on average closer together in solution than they are in the crystal structure. This interpretation was evident in the P(r) profile, which showed a peak with a shoulder in the distribution rather than the two resolved peaks indicative of two separate domains and suggested that, like calmodulin, the helix connecting the two globular EF-hand domains was flexible in solution.…”
Section: Skeletal and Cardiac Isoforms Of Troponinmentioning
confidence: 99%
“…SANS studies of the ternary cTn further revealed the effect of phosphorylation of the two protein kinase A dependent phosphorylation sites in the cardiac-specific N-terminal extension in cTnI ($ 27-33 residues); this phosphorylation in known to result in a reduction in myofilament Ca 21 sensitivity and an increase in relaxation and cross-bridging cycle kinetics. [25][26][27] All of the high-resolution structures of sTnC and cTnC show the characteristic dumbbell shape with two globular domains separated by an extended, solvent-exposed helix of 7-8 turns [28][29][30][31][32] 41 and Heidorn and Trewhella 42 presented the first SAXS studies of rabbit sTnC that showed that the two globular domains of sTnC are on average closer together in solution than they are in the crystal structure. This interpretation was evident in the P(r) profile, which showed a peak with a shoulder in the distribution rather than the two resolved peaks indicative of two separate domains and suggested that, like calmodulin, the helix connecting the two globular EF-hand domains was flexible in solution.…”
Section: Skeletal and Cardiac Isoforms Of Troponinmentioning
confidence: 99%
“…The first three-dimensional structure of skeletal TnC (sTnC) was solved by X-ray crystallography in 1985 [4,5]. In this structure, the two N-domain (sNTnC) Ca 2+ -binding sites were unoccupied, while the C-domain (sCTnC) was in two Ca 2+ -bound state.…”
Section: Introductionmentioning
confidence: 99%
“…This is in sharp contrast to other calcium binding proteins such as calmodulin (25,26), troponin C (27,28), and calbindin (29) or other Gla-containing proteins (1)(2)(3). A high-resolution structure of Ca 2+ -osteocalcin will provide information on a new class of proteins.…”
mentioning
confidence: 96%